Current status and influencing factors of mild renal function decline in elders aged over 60 years - Xue Jian-qiang; He Na; Shuai Ping; Liu Yu-ping (Linchuang shenzangbing zazhi)
ObjectiveTo provide basic rationales for guidelines and recommendations on screening and management of renal function in elders by collecting the relevant data of physical examination subjects aged over 60 years，retrospective analysis was made for mild renal function decline during physical examination of subjects aged over 60 years so as to understand the situation of mild renal function decline in elders.MethodsBased upon the results of 13，251 people aged 60-95 participating in physical examination at Health Management Center from 2018 to 2020，elders with mild renal function decline were divided into two groups according to the level of estimated glomerular filtration rate （eGFR）. The relevant parameters and influencing factors of renal function in each group were examined.ResultsA total of 7553 elderly subjects were collected. Comparing mild renal function decline and normal renal function，no significant differences existed in gender，age group，weight，systolic blood pressure grade，proteinuria，diabetes，hypertension，renal calculus，renal cyst，hyperlipidemia，abnormal liver function and hematuria between two groups （P>0.05）. No significant differences existed in age，body mass index，systolic blood pressure，total cholesterol，triglyceride，low density lipoprotein cholesterol，high-density lipoprotein，alanine aminotransaminase，aspartate aminotransaminase，total bilirubin，direct bilirubin，indirect bilirubin，albumin，globulin，fasting glucose or total protein （P>0.05）.Compositions of hematuria and hyperuricemia and levels of age，diastolic blood pressure，hemoglobin，urea nitrogen and low density lipoprotein were statistically different （P<0.05）. With lowered renal function as adependent variable，compositions of hematuria and hyperuricemia，age，diastolic blood pressure，hemoglobin，urea nitrogen，low density lipoprotein and uric acid value were included for multivariate Logstic regression analysis. Statistically significant differences existed in hemoglobin （OR 0.998，95%CI 0.473~0.641），urea nitrogen （OR 1.369，95%CI 1.310-1.431） and uric acid （OR 0.935，95%CI 0.912~0.959） （P<0.05）.ConclusionsKidney health is critical in people aged over 60 years. Kidney function should be screened on a routine basis.